The Role of Antibiotic-Killed Staphylococcus aureus and Its DNA to Cause Arthritis in Rats - S. Saeed Malalah, Sara; M. Utba, Nawal; F. Al-Mathkhury, Harith. J. (Iraqi Journal of Science, 2023)
The purpose of this study is to investigate the capability of bacterial DNAcompared to bacterial lysate in stimulating arthritis using rat model. One hundredmid-stream urine specimens were collected during November 2012 to January 2013,from patients suffering from urinary tract infections attending hospitals in Baghdad,Iraq. Susceptibility of Staphylococcus aureus isolates to antibiotics was examined.Twenty five isolates were identified as S. aureus and they developed multi drugresistance. S. aureus S1 lyaste and its DNA were intra-articulary injected in rats. Thelevels of IL-6, anti-ds DNA Ab and leukocytes count were measured. In general, IL-6, anti-ds DNA Ab and leukocytes count were significantly higher in sera of ratsinjected with cell lysate. Moreover, time period significantly (P< 0.05) affected theimmunological aspects and joints damage. In a conclusion, bacterial lysate causedmore damage to rat joints than DNA. Furthermore, bacterial lysate evokedimmunological parameters more than DNA did.